Data from: Influence of clay licks on the diversity and structure of an Amazonian forest - Molina, Eduardo; Espelta, Josep Maria; Pino, Joan; Bagaria, Guillem; Armenteras, Dolors (Dryad, 2018)
The spatial heterogeneity of resource availability is a major driver of
biodiversity patterns. Some environmental conditions and resources are
characterized by large-scale patterns of variation within the landscape.
Clumped local discontinuities or discrete elements also increase spatial
heterogeneity, romoting local “biodiversity hot-spots” by modifying
habitat characteristics and promoting plant-animal interactions. Clay
licks are faunal attractors owing to their role in the nutritional ecology
of the user species; nevertheless, the effect of their presence on the
surrounding vegetation has been poorly quantified. Here, we use data from
100 x 10 m transects and evaluate the effects of the presence of clay
licks on forest diversity and structure at local and landscape scales. In
clay lick areas, there was a higher abundance of certain species, which
helps to homogenize species composition between localities counteracting
the natural distance-decay of compositional similarity between transects
without clay lick influence (controls). Compared to control sites, clay
lick´s forests had higher palm densities, shorter but more variable
individuals in the canopy and understory, a thinner canopy layer, and
denser herbaceous and ground level covers. These differences were found
along the whole length of transects in both sampled areas types. These
results reveal that the presence of discrete elements (i.e. clay licks)
may help to explain the compositional and structural heterogeneity of
Amazonian forests influencing ecological processes such as seed dispersal
and trampling. These considerations may be relevant for other biomes where
clay licks are present and give weight to their inclusion in conservation
initiatives in tropical forests.
Inventory_sppSpecies invetontory of each plot of each transect at clay
licks and non clay licks areas.Plot_coverage_StructurePlant covers of each
plot of each transect in clay lick and non clay lick
areasPlot_Trees_StructureStrucutural attributes of individuals of each
plot of each transect in clay lick and non clay lick areas
Keywords: Geophagy; Cenozioc; Valcular plants; Spatial heterogeneity.; Forest engineering; Keystone landscape elements